(untitled) (Fiep Bulletin - online, 2015)
I – Work has assumed a major role in the life of modern man My purpose is to deal with the man who works and with interesting results of physical education and sports. Our modern world is characterized by the need to work that has been imposed on the vast majority of individuals.